Introduction: International information issues and ASIS&T. Issue 5 (19th June 2014) - Alemneh, Daniel Gelaw; Rorissa, Abebe
Abstract: EDITOR'S SUMMARY Since 1937 ASIS&T has promoted sharing within the information science community, a goal made more critical in an expanded, globalized environment. The Association's increasingly international reach stimulates discussion of global issues and challenges, lays a foundation for future growth and has prompted the development of Special Interest Group/International Information Issues (SIG/III). SIG/III has been active in member recruitment internationally and organizes the International Paper Contest to stimulate research and sharing at a global level. Devoted to international issues, this special section features interviews with SIG cofounders and leaders in information science, a discussion of ASIS&T chapters and SIGs and their role in strengthening the Association, virtual networking activities and past and current organizational initiatives. Massively open online courses (MOOCs) that aid the globalization of education, indigenous perspectives that expand our thinking and the pervasiveness of information policy elements all reinforce the international relevance of the field and the Association.